Improvement of effectiveness in active triangular plate vibration reduction - Adam BRAŃSKI; Stanisław SZELA (Archives of Acoustics, 2008)
In the paper, a new method of the effectiveness increase of the active asymmetrical structure vibration reduction via PZTs is proposed. The new method is based on adding successive PZTs to quasi-optimal sub-areas (QO) in the determined order. A triangular plate with the C-F-F boundary conditions is chosen for this purpose. Only the second mode of the plate is taken into consideration in this study. To realise the aim, first the QO are determined. To each QO, PZTs are bonded from one to seven according to the following rule; namely, the consecutive PZT takes up free surface with locally maximal curvature on the QO. The effectiveness of the vibration reduction is measured in particular sense. Numerical experiments are performed to confirm the validity of this idea.